History re-written: Misconceptions of U.S. trade and industrial policy and the influence of neoliberalism - Travis K. Taylor; Amanda Montera (Review of Economic Perspectives, 2021)
A disparity exists between mainstream perception and reality with regard to American economic history. There is widespread belief among the public, media, and even some scholars that the U.S. amassed its wealth and prosperity from the adoption of exclusively free-market principles from the onset of the union. This is far from reality. Since 1980, the U.S. government has adopted policies that largely support the free-market ideology and can be classified as neoliberal. However, As Chang (2002) and Cohen and DeLong (2016) have shown, during the early stages of economic development and critical junctures whilst a middle-income country, the U.S. record is one of active government intervention in targeted industries, the creation of important institutions to complement free-market competition, and the widespread use of trade protection in support of infant industries. This misconception has significant ramifications for present-day developing countries, which are routinely advised to adopt neoliberal policies with insufficient regard for the idiosyncratic stage of economic development. This paper documents the misconceptions by examining the theoretical basis and historical record of U.S. industrial and trade policy. We detail how this misconception became widespread and ultimately entered policymaking by analyzing two contributing factors: the rise of neoliberalism, and the standard economics curriculum.
Keywords: B1; B5; O2; 330; neoliberalism; American economic history; industrial policy; trade policy; economic education